1976
DOI: 10.1037/0033-2909.83.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal assessment of Piagetian concepts.

Abstract: A common criticism of Piagetian assessment is that the language used may lead to an underestimation of the young child's ability. Studies are reviewed which attempt to reduce linguistic or other performance demands in the assessment of Piagetian concepts. It is argued that a precise diagnosis of cognitive skills is important for several reasons: for testing claims concerning the sequencing or concurrence of cognitive acquisitions, for assessing the effects of training or educational interventions, and for eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…As a result of these methodological considerations, the trend in cognitive-developmental psychology has been to ignore children's verbal justifications more or less entirely and to focus instead on judgments only or on various "nonverbal" assessment procedures (Braine, 1959;Brainerd, 1973;Siegel, 1978). Unfortunately, the results obtained through such procedures have been subject to interpretive ambiguities of their own (Larsen, 1977;Miller, 1976).…”
Section: Reinterpreting Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these methodological considerations, the trend in cognitive-developmental psychology has been to ignore children's verbal justifications more or less entirely and to focus instead on judgments only or on various "nonverbal" assessment procedures (Braine, 1959;Brainerd, 1973;Siegel, 1978). Unfortunately, the results obtained through such procedures have been subject to interpretive ambiguities of their own (Larsen, 1977;Miller, 1976).…”
Section: Reinterpreting Previous Resultsmentioning
confidence: 99%
“…For these reasons, investigators have attempted to infer the character of children's cognitive processes through a variety of indirect, nonverbal methods (Braine, 1959;Brainerd, 1973;Siegel, 1978). However, the use of such methods has been questioned on the grounds that they might not measure what they were intended to measure originally (Larsen, 1977;Miller, 1976).…”
mentioning
confidence: 99%
“…On the other hand, this criticism has not gone unchallenged. Miller [1976] reviewed alternative ways of assessing Piagetian concepts and concluded that there was little evidence that most of them were attained earlier than Piaget had predicted. We will not attempt to cover this vast data base but will consider a few of the more important issues.…”
Section: Preschool Children's Thoughtmentioning
confidence: 99%
“…Accompanying this conceptual restructuring there have been a number of methodological reassessments (Halford, 1984;Miller, 1976;Perner, Steiner, & Staehelin, 1981;Silverman & Briga, 1981). One example is the conservation concept.…”
mentioning
confidence: 99%